Food taboo of taking pineapple and milk at a time - Rahman, Md. Mahbubur (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
The purpose of this study was to assess whether potential toxic interactions occur between the pineapple and milk following oral administration in rats by comparing clinical signs, hematological and biochemical parameters with the normal control and toxic standard groups. Pineapple and milk solutions were made by 1:1 (PMS1) and 2:1 (PMS2) ratio, administered 12 mL/kg body weight. Forty rats were equally divided into 4 groups treated for 3 days: a) normal control (only vehicle treated); b) toxic standard (CCl4 was suspended in corn oil, 20% v/v; treated 1.25 mL/kg), c) PMS1 and d) PMS2 groups. CCl4 administration altered the normal behavior, changes gross and microscopic morphology. Toxicity related hematological and serum biochemistry changed significantly (p<0.05) than the normal group. However, all these clinical and pathological changes were completely absent in PMS treated groups. These results suggest that taking pineapple with milk is not toxic and this food taboo is wrong.